Shock therapy to treat the Novel Coronavirus Disease (COVID-19) by ddNTPs - Yeping Tan (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
The Novel Coronavirus (SARS-CoV-2) has caused a massive global outbreak, presenting a significant public health emergency and international concern. Thousands of critically ill patients are dying daily. To date, there are no clinically approved antiviral drug available to cure the Novel Coronavirus infections.  I highly recommend the clinical trial of 2',3'-dideoxyribonucleoside triphosphate (ddNTPs, except ddTTP) to be used for the Novel Coronavirus Disease (COVID-19) antiviral therapy.